2021
DOI: 10.12688/f1000research.54306.1
|View full text |Cite
|
Sign up to set email alerts
|

Toxin-like peptides in plasma, urine and faecal samples from COVID-19 patients

Abstract: Background: SARS-CoV-2 that causes COVID-19 disease and led to the pandemic currently affecting the world has been broadly investigated. Different studies have been performed to understand the infection mechanism, and the involved human genes, transcripts and proteins. In parallel, numerous clinical extra-pulmonary manifestations co-occurring with COVID-19 disease have been reported and evidence of their severity and persistence is increasing. Whether these manifestations are linked to other disorders co-occur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
34
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 22 publications
(39 citation statements)
references
References 40 publications
5
34
0
Order By: Relevance
“…They observed that bacterial endotoxins induced a lower rate or even inhibited viral replication [ 35 ]. Similar to our studies [ 6 , 7 ], we highlighted several toxin-like proteins in the plasma, feces, and urine of COVID-19 patients, which were produced by bacteria as a consequence of interaction with SARS-CoV-2. We have shown that these oligopeptides are derived from bacterial cultures [ 6 , 7 ] and we are testing them in mice (data in preparation).…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…They observed that bacterial endotoxins induced a lower rate or even inhibited viral replication [ 35 ]. Similar to our studies [ 6 , 7 ], we highlighted several toxin-like proteins in the plasma, feces, and urine of COVID-19 patients, which were produced by bacteria as a consequence of interaction with SARS-CoV-2. We have shown that these oligopeptides are derived from bacterial cultures [ 6 , 7 ] and we are testing them in mice (data in preparation).…”
Section: Discussionsupporting
confidence: 87%
“…To deepen our previous studies [ 6 , 7 ], analyses using immunofluorescence, TEM, and immunogold marking techniques were conducted. These analyses showed infection of bacteria by the SARS-CoV-2 virus after 30 days of bacterial culture, where mammalian eukaryotic cells are excluded, in agreement with current literature that excludes their survival beyond 48 h [ 20 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In line with previous observations [ 30 , 31 , 32 ], the oral therapy adopted was amoxicillin with clavulanic acid 3 g/day for three days and 2 g/day for another three days, associated with azithromycin 500 mg/day for six days. As supplements, he took vitamin C (2 g/day for seven days), vitamin D (25,000 I.U.…”
Section: A Brief Description Of the Casesupporting
confidence: 74%
“…Furthermore, an intriguing correlation has been found between the toxin-like peptides and the samples collected from COVID-19 patients. Among all the peptides identified, conotoxin-like peptides are ubiquitous: sequences from Conus tulipa (P), Conus geographus (P), Conus marmoreus (M), Conus radiatus (V/P), Conus virgo (V), Conus quercinus (V), Conus pulicarius (V), Conus flavidus (V), Conus catus (V) and Californiconus californicus (V/M/P) have been identified in plasma, urine and fecal samples of COVID-19 patients [76]. This might explain the occurrence of many neurotic related symptoms observed in some COVID-19 patients, such as hyposmia, hypogeusia and signs typical of the Guillain-Barre syndrome.…”
Section: Potential Value In Covid-19 and Other Diseasesmentioning
confidence: 99%